Leadership Behavior as the Determinant of Organizational Engagement: A Review of Managerial Character and Employee Retention - ., Barika; Elliyana, Ela; Basir, Abdul; ., Arfan (Journal of Cultural Analysis and Social Change, 2025)
This conceptual study aims to examine how leadership behavior and managerial character serve as key determinants of organizational engagement and employee retention. Using a conceptual study approach, this study integrates findings from Social Exchange and Leader–Member Exchange (LMX) theories to explain the psychological relationship mechanism between leaders and subordinates. The synthesis results show that character-based leadership behavior including integrity, empathy, fairness, empowerment, and emotional support can create high-quality social relationships that increase engagement. This attachment then functions as a psychological mediator that bridges leadership behavior and employees' decisions to stay. These findings show that retention is determined more by the quality of social experiences and a sense of belonging in the organization than by financial incentives alone. This study produces a new conceptual model that positions engagement as the main link in the relationship between leadership and retention. This model provides relevant theoretical and practical contributions to organizations, particularly in designing character-based leadership development programs and relationship-oriented retention strategies. Recommendations for further research include empirical testing, mixed-methods approaches, the addition of moderating variables, and exploration of cultural contexts and future generations of workers.